PENGARUH KEMIRINGAN BATAS HORISON TERHADAP WAKTU PELONGSORAN PADA TANAH DOMINAN DEBU DAN LIAT - Sandy Budi Wibowo; W Widianto; S Sudarto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2014)
Landsliding duration is the time span between saturated soil condition and landslide in seconds. It is a parameter to describe failure process. Horizon boundary declivity is a broad in horizon boundary formed an angle toward the horizontal and assumed parallel with slope surface.Landsliding duration can be measured by way of landslide simulation to saturated soil sample through artificial rain with 50 mm hour-1 intensity up to landslide. Soil sample taken as a whole by pipe. This treatment consisted of 40o and 70o horizon boundary declivity and repeated 10 times. Soil sampling conducted at 4 locations divided by 2 locations with silt domination and 2 locations with clay domination. Beside that, qualitative observation performed of process and mass movement as well.The result of observation has shown that landsliding duration at 40o horizon boundary declivity is slower than 70o. Gravitation forces has characteristic of holding soil mass at 40o horizon boundary declivity, but at 70o horizon boundary declivity it will cause landslide. Medium texture will landslide faster than fine texture at 40o horizon boundary declivity. But at 70o horizon boundary declivity both of medium and fine texture will landslide together. Due to that 70o horizon boundary declivity dominated by gravitation force that pull soil mass to the downslope. While at 40o horizon boundary declivity, soil physics nature is still have a role, where fine texture have characteristic of sticky and medium texture have a quality of slick.Translational slides happen at 70o horizon boundary declivity so many times. While topples usually happen at 40o horizon boundary declivity. This cause of at 40o horizon boundary declivity soil physics nature still have a role of landslide, while at 70o horizon boundary declivity gravitation forces pull soil mass more dominant. But if it related with texture, translational slides usually happen at medium texture and topples happen at fine texture so many times. Landslide process at fine texture is preceded by cracks forming ended by topples. While landslide process at medium texture is preceded by smooth erosion on soil surface and soil liquefaction at upper side of horizon boundary because of the water is not able to penetrate beneath horizon.Key words: lansliding duration, horizon boundary declivity, texture